Remifentanil in labor - Basavana Gouda Goudra; Preet Mohinder Singh (Wolters Kluwer Medknow Publications, 2013)
Remifentanil is in clinical use for over 15 years. In spite of its unparalleled popularity, largely due to its unique pharmacokinetics, its place in labor analgesia is yet to be determined. Narrow therapeutic window and ability to cause rapid and severe respiratory depression are some of the major setbacks. Need for close monitoring, at least in the initial implementation stage is mandatory. Education of the labor suite nurses along with innovative monitoring technique is needed to realize the full potential of remifentanil in the labor room.